The foundations of vacuum coating technology - Mattox, D. M. (Noyes Publications : William Andrew Pub., 2003)
The Foundations of Vacuum Coating Technology is a concise review of the developments that have led to the wide variety of applications of this technology. This book is a must have for materials scientists and engineers working with vacuum coating in the invention of new technologies or applications in all industries. With over 370 references, this is an excellent starting point for those who don't want to reinvent the wheel. In particular, the book is a valuable reference for those interested in researching proposed or existing patents. This unique book provides a starting point for more in-depth surveys of past and recent work in all aspects of vacuum coating. The author uses his extensive knowledge of the subject to draw comparisons and place the information into the proper context. This is particularly important for the patent literature where the terminology does not always match industry jargon. A section of acronyms for vacuum coating and glossary of terms at the end of the book are critical additions to the information every reader needs.